Arthroscopic Bankart Repairs With and Without Remplissage in Recurrent Adolescent Anterior Shoulder Instability With Hill-Sachs Deformity. Issue 12 (10th December 2018) - Hughes, Jessica L.; Bastrom, Tracey; Pennock, Andrew T.; Edmonds, Eric W.
Background: Recurrent shoulder dislocation after surgical intervention in adolescents with anterior instability is now understood to occur with a relatively high frequency. The remplissage procedure is successfully used in the adult population to mitigate the ability of a Hill-Sachs lesion to engage the anterior glenoid and can be used during an arthroscopic Bankart repair for anterior shoulder instability. Purpose: To compare the clinical outcomes in adolescent patients who underwent a Bankart repair with or without remplissage for treatment of recurrent anterior shoulder instability and associated Hill-Sachs defects. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review was conducted on adolescents who underwent a remplissage procedure for recurrent anterior shoulder instability from 2009 to 2017 at a single institution. Controls were identified in a cohort of patients who underwent a Bankart repair only and were matched based on age, sex, and size of Hill-Sachs lesion. All patients were then contacted to determine instability recurrence as well as to complete the shortened version of the Disabilities of the Arm, Shoulder and Hand (QuickDASH) and the Pediatric Adolescent Shoulder Score (PASS) outcome surveys. Results: Twenty-one adolescents underwent a remplissage procedure, and 20 matched controls underwent only a Bankart procedure. A significantly higher rate of recurrence was noted in the Bankart-only patients (8/17) compared with remplissage patients (2/15) ( P = .04). No statistical difference was found in patient-reported outcome scores between treatment groups or in range of motion measurements ( P > .05). In a subset of patients in the remplissage group with pre- and postoperative surveys available, mean ± SD scores for PASS (77 ± 11) and QuickDASH (19 ± 12) improved when compared with preoperative scores (PASS, 54 ± 16; QuickDASH, 35 ± 28), but only the PASS score was statistically improved (PASS, P = .003; QuickDASH, P = .23). Conclusion: The addition of the remplissage procedure to a Bankart repair is a reasonable surgical option to treat a Hill-Sachs deformity in adolescents with anterior shoulder instability. The success of this additional procedure may be due to filling the Hill-Sachs defect, or perhaps it augments stability through a mechanism of posterior capsulorrhaphy. Either way, this young athletic population appears to have a lower rate of recurrence and improved patient-reported outcomes with a remplissage procedure to address the Hill-Sachs deformity.